The Banff 2015 Kidney Meeting Report: Current Challenges in Rejection Classification and Prospects for Adopting Molecular Pathology. Issue 1 (January 2017) - Loupy, A.; Haas, M.; Solez, K.; Racusen, L.; Glotz, D.; Seron, D.; Nankivell, B. J.; Colvin, R. B.; Afrouzian, M.; Akalin, E.; Alachkar, N.; Bagnasco, S.; et al.
Abstract : The XIII Banff meeting, held in conjunction the Canadian Society of Transplantation in Vancouver, Canada, reviewed the clinical impact of updates of C4d‐negative antibody‐mediated rejection (ABMR) from the 2013 meeting, reports from active Banff Working Groups, the relationships of donor‐specific antibody tests (anti‐HLA and non‐HLA) with transplant histopathology, and questions of molecular transplant diagnostics. The use of transcriptome gene sets, their resultant diagnostic classifiers, or common key genes to supplement the diagnosis and classification of rejection requires further consensus agreement and validation in biopsies. Newly introduced concepts include the i‐IFTA score, comprising inflammation within areas of fibrosis and atrophy and acceptance of transplant arteriolopathy within the descriptions of chronic active T cell–mediated rejection (TCMR) or chronic ABMR. The pattern of mixed TCMR and ABMR was increasingly recognized. This report also includes improved definitions of TCMR and ABMR in pancreas transplants with specification of vascular lesions and prospects for defining a vascularized composite allograft rejection classification. The goal of the Banff process is ongoing integration of advances in histologic, serologic, and molecular diagnostic techniques to produce a consensus‐based reporting system that offers precise composite scores, accurate routine diagnostics, and applicability to next‐generation clinical trials. Abstract : In this article, the Banff consortium presents the most updated version of the kidney, pancreas, and VCA transplant rejection classification and prospects for implementing intragraft molecular assessment. See the companion report onpage 42 .